Mental-Emotional Disorder among Post-Earthquake Responders in Ambon Maluku - Cut Mutia Tatisina; Ahmad An Naufal; Hamdan Hariawan (Universitas Airlangga, 2020)
Introduction: The purpose of this study was to explain the factors related to mental-emotional disorder among post-earthquake responders in Ambon, Maluku. Methods: The design was observational analytics with a cross-sectional approach. Respondents were 174 people living near the epicenter and taken by simple random sampling. The independent variables were age, sex and work status, damage to the residence, the family members dying from earthquakes, and assistance from the government. The dependent variable was mental-emotional disorders. Data of mental-emotional disorder were collected using the SRQ 20 (Self-Reported Questionnaire) and analyzed using logistic regression (α <0.05).Results: The results showed 69% of respondents experienced mental-emotional disorders. Communities who were 17-25 years (OR = 0.05; 95% CI = 0.005 - 0.491) tend to experience mental-emotional disorders. Communities with moderate category of residence damage (OR = 0.313; CI95% = 0.115 - 0.856) tend to experience mental-emotional disorders. Communities with family members dying from earthquakes (OR = 2,616; CI95% = 1,228 - 5,577) tend to experience mental-emotional disorders. Communities who did not get residence compensation (OR = 2,575; CI95% = 1,073 - 6,177) tend to experience mental-emotional disorders.Conclusion: There were factors related to mental-emotional disorder among post-earthquake victims, such as teenagers who were 17-25 years old, community with residence damage and injured or died family members, and those who did not get assistance. Assisting still needs to be done to prevent mental-emotional disorders of people affected by earthquake.